Butelase 1: A Versatile Ligase for Peptide and Protein Macrocyclization - Nguyen, Giang K. T; Kam, Antony; Loo, Shining; Jansson, Anna E; Pan, Lucy X; Tam, James P (Journal of the American Chemical Society, 2015)
Macrocyclization is a valuable tool for drug design and protein engineering. Although various methods have been developed to prepare macrocycles, a general and efficient strategy is needed. Here we report a highly efficient method using butelase 1 to macrocyclize peptides and proteins ranging in sizes from 26 to >200 residues. We achieved cyclizations that are 20,000 times faster than sortase A, the most widely used ligase for protein cyclization. The reactions completed within minutes with up to 95% yields.